STRATEGI MITIGASI DAN ADAPTASI TERHADAP PERUBAHAN IKLIM: STUDI KASUS KOMUNITAS NAPU DI CAGAR BIOSFER LORE LINDU - Purwanto, Y.; Suryanto, J. (P2KK LIPI, 2012)
Global climate change influences poverty phenomena and will be a challenge to community because its impact in the loss of biodiversity and ecosystem degradation. Ecosystem degradation that is brought about by climate change will affect the communities that depend on biodiversity for their livelihoods. The objective of this study are to gather knowledge and Napu community capabilities regarding to develop adaptation strategy in order to manage their biological resources. The study conducted in 2012 in Napu valley area, in the buffer zone and transition area of Lore Lindu Biosphere Reserve shows that communities have good knowledge about biodiversity and ecosystem types and spatial arrangement. Napu community knows and beliefs that climate change is the indicator of unpredictable temperature, dry season, rain season, and quantity of precipitation. Based on those conditions Napu community develops adaptation strategy with cultivation development, mixed cropping, changed in the varieties of crops, and other technique. Keywords: adaptation strategy, natural and biological resources management, climate change, Napu community Lore Lindu biosphere reserve